Macroeconomic Profitability: Theory and Evidence - Thomas R. Michl (Levy Economics Institute of Bard College, 1987)
This paper gives an account of recent work on the measurement, statistical analysis, and theoretical analysis of macroeconomic profitability. Measurement issues include the treatment of holding gains on physical assets and net financial liabilities, national income accounting practices and recent revisions, and the use of accounting rates of return. Statistical work has focused on the identification of trends and shifts in profit rates not caused by cyclical fluctuations, and various theoretical explanations have been offered for the generally low rates of return that appeared in the 1970s. These include capital deepening stimulated by a reduction in the cost of capital funds; profit squeezes caused by some combination of slower productivity growth, real wage push, and raw material price inflation; declining capital productivity; and changes in effective tax rates. The paper raises several questions. The use of a constant mark-up pricing model in reduced form to control for cyclical effects on profitability is questioned because of evidence that the mark-up is variable, and some suggestions for incorporating this evidence into applied studies of profitability are offered. Several empirical puzzles are identified. The apparent decline in capital productivity is one; the more pronounced decline in before-tax profitability compared to after-tax profitability is another.
Keywords: 330